2017
DOI: 10.1371/journal.pone.0174114
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of betahistine (48 mg/day) in patients with vestibular vertigo during routine practice: The VIRTUOSO study

Abstract: BackgroundVestibular vertigo is associated with substantially reduced quality of life. Betahistine is effective in improving vertigo-associated symptoms, with longer treatment periods leading to greater improvements; however, it is not known whether these effects persist after treatment cessation.MethodsVIRTUOSO was a prospective, multinational, non-comparative, post-marketing observational programme investigating the effectiveness of betahistine (48 mg/day) and the course of vertigo after the discontinuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 11 publications
3
18
0
3
Order By: Relevance
“…It is worth noting that although not all patients achieved complete improvement, the average improvement at the end of the follow-up was 89 points on a scale of 0 to 100. These results in addition to supplementing the clinical effectiveness data published in some previously cited studies [12][13][14] are consistent with what was reported in a multicenter observational study published in 2017, conducted in Russia and Ukraine by Parfenov et al, 11 in which 305 patients were included of which 74% achieved a clinical response considered good, very good, or excellent. The findings documented in previous research, as well as those described by us in the present work, can be explained by the mechanism of action of betahistine, which includes among others a histaminergic vasodilator effect of the cerebral and inner ear microcirculation as well as by its action at the level of the central histaminergic system, which improves the process of vestibular compensation and reduces the spontaneous activity of peripheral vestibular receptors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is worth noting that although not all patients achieved complete improvement, the average improvement at the end of the follow-up was 89 points on a scale of 0 to 100. These results in addition to supplementing the clinical effectiveness data published in some previously cited studies [12][13][14] are consistent with what was reported in a multicenter observational study published in 2017, conducted in Russia and Ukraine by Parfenov et al, 11 in which 305 patients were included of which 74% achieved a clinical response considered good, very good, or excellent. The findings documented in previous research, as well as those described by us in the present work, can be explained by the mechanism of action of betahistine, which includes among others a histaminergic vasodilator effect of the cerebral and inner ear microcirculation as well as by its action at the level of the central histaminergic system, which improves the process of vestibular compensation and reduces the spontaneous activity of peripheral vestibular receptors.…”
Section: Discussionsupporting
confidence: 90%
“…For the sample size calculation, the formula proposed by Lemeshow et al was used to estimate a proportion, including the desired precision. 10 Based on the results of the study carried out by Parfenov et al, 11 we assume a 90% expected clinical effect for betahistine, with a level of accuracy of 5% and a type I error of 5%, plus a 10% adjustment for potential losses, we obtained a final sample size of 150 patients.…”
Section: Population and Samplementioning
confidence: 99%
“…In the present study, we found that up to 24 (85.71%) of patients got benefit after the first follow-up visit of one week. In a study from Turkey, they found 86.2% of patients were improved after a single session with Epley maneuver 22 . In a study done by Parfenov week.…”
Section: Discussionmentioning
confidence: 96%
“…О Б З О Р Ы Исследование VIRTUOSO продемонстрировало эф-фективность бетагистина в дозе 48 мг/сут для лечения вес-тибулярного головокружения в амбулаторной практике [24]. Примерно в 4% случаев при обследовании пациента не удается установить причину головокружения.…”
Section: неврология нейропсихиатрия психосоматика 2018;10(1):96-101unclassified